Identifikasi Masalah Air intake Dan Exhaust Serta Uji Dynotest Engine C15 Caterpillar Pada PT Trakindo Utama Surabaya - Afero Pranesti, Dennova; Puspitasari, Dewi; Yasa Utama, Firman; Mahendra Sakti, Arya (Universitas Negeri Surabaya, 2025)
This study aims to identify problems in the air intake and exhaust systems and to evaluate the performance of a Caterpillar C15 diesel engine through engine dynamometer testing at PT Trakindo Utama Surabaya. The method involved technical observation, dynamometer testing under various load conditions, and analysis of engine performance parameters, including power, torque, engine speed, oil pressure, fuel pressure, and boost pressure. The test results indicate that increasing load leads to proportional increases in power, torque, and boost pressure, while engine speed decreases at high loads without indicating abnormalities in the lubrication and fuel supply systems. Problem identification reveals that performance degradation is mainly associated with the valve mechanism and combustion instability, as indicated by improper valve lash and excessive white smoke from the exhaust system. The application of step-by-step troubleshooting procedures in accordance with manufacturer specifications proved effective in determining appropriate corrective actions and restoring engine performance to optimal conditions. This study provides a solid technical basis for implementing preventive and corrective maintenance strategies for Caterpillar C15 engines in heavy-duty industrial applications.